ustainability criteria for Brazilian Clean Development Mechanism projects - Kulay, Luiz Alexandre; Miraglia, Simone Georges El Khouri; Hummel, Natalia Lutti (Revista Gestão da Produção Operações e Sistemas, 2009)
The great concern related to Global Warming has forced society to develop several initiatives that focus on pro- posing solutions. Among these initiatives, the Kyoto Protocol is the most effective. This document portrays three mechanisms for approaching Greenhouse Gas (GHG) emissions. The most important is called the Clean De- velopment Mechanism (CDM), which proposes to reduce the generation of such rejects by implementing clean technologies in developing countries, contributing to sustainable development and generating credits that can be commercialized with developed countries. In Brazil, the approval of CDM projects is due to Interministerial Commission on Global Climate Change (ICGCC), a public institution at the federal level which deliberates on the elegibility of these projects. This study aims at analyzing the mecanisms and procedures utilized by ICGCC in terms of sustainability of such iniatives and proposing criteria tied to a point system. Thus, projects will have more transparency, objectivity and provide a greater contribution to sustainable development. In this sense, we used Brazilian CDM projects related to Fuel Substitution as an object for critical analysis. Keywords: Clean Development Mechanism; Interministerial Commission on Global Climate Change; Annex III; Environmental Management; Sustainable Development